2009
DOI: 10.3109/09638280903186301
|View full text |Cite
|
Sign up to set email alerts
|

Workplace involvement improves return to work rates among employees with back pain on long-term sick leave: a systematic review of the effectiveness and cost-effectiveness of interventions

Abstract: Stakeholder participation and work modification are more effective and cost effective at returning to work adults with musculoskeletal conditions than other workplace-linked interventions, including exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
144
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 176 publications
(150 citation statements)
references
References 45 publications
1
144
1
4
Order By: Relevance
“…The final total of unique publications citing the key paper one or more times within their text was 393. For details of the search process and its results, see the flowchart in the Figure. There was only 2/393 instances of self-citation (Carroll et al 2010;Booth 2008) and one of citation by an author's colleague (Leaviss and Uttley 2015). The break-down of these citing publications by publication type is reported in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…The final total of unique publications citing the key paper one or more times within their text was 393. For details of the search process and its results, see the flowchart in the Figure. There was only 2/393 instances of self-citation (Carroll et al 2010;Booth 2008) and one of citation by an author's colleague (Leaviss and Uttley 2015). The break-down of these citing publications by publication type is reported in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Economic modelling based on this review found that any intervention which returns at least an additional 3% of employees to work and costs less than an additional £3000 per employee is likely to be considered economically attractive compared with usual care, relative to other interventions routinely funded by the NHS. 9 A further review of the evidence for workplace involvement on return-to-work rates following long-term sickness absence 10 found that only a particular type of workplace involvement intervention was consistent in achieving positive return-to-work results. The evidence was limited to employees with back pain and found that active, structured consultation among employee, employer and OH practitioners, and agreements regarding subsequent, appropriate work modifications, appear to be more effective at helping employees on long-term sickness absence to return to work than those interventions which lack such components.…”
Section: Current Evidence On Return-to-work Interventionsmentioning
confidence: 99%
“…Fewer cases per SIO might therefore help to increase the number of cooperations with workplaces. Although this initially will require more resources, it might turn out to be more effective in the end, as studies consistently have found that interventions involving the workplace, to -for example -implement work modifications, were more effective than interventions not involving the workplace (29,30). The most recent change in the Danish sickness benefit scheme, which took effect in …”
Section: Aust Et Almentioning
confidence: 99%